2021
DOI: 10.3389/fonc.2021.736546
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Circulating Circular RNA in Cancer Diagnosis, Monitoring, Prognosis, and Guiding Treatment

Abstract: Liquid biopsy includes non-invasive analysis of circulating tumor-derived substances. It is a novel, innovative cancer screening tool that overcomes the limitations of current invasive tissue examinations in precision oncology. Circular RNA (circRNA) is a recent, novel, and attractive liquid biomarker showing stability, abundance, and high specificity in various diseases, especially in human cancers. This review focused on the emerging potential of human circRNA in body fluids as the liquid biopsy biomarkers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 129 publications
0
14
1
Order By: Relevance
“…In particular, in the current era of the precision medicine, the need to use the so-called “liquid biopsy” like easily accessible body fluids provides great advantages since the collection process is less invasive than tissue collection, and can be reiterated over the time in the processes of follow-up and real-time monitoring of the patients. In addition, the metabolites contained in the liquid biopsies have the power of mirroring multiple biochemical processes and pathways happening in tissues [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the current era of the precision medicine, the need to use the so-called “liquid biopsy” like easily accessible body fluids provides great advantages since the collection process is less invasive than tissue collection, and can be reiterated over the time in the processes of follow-up and real-time monitoring of the patients. In addition, the metabolites contained in the liquid biopsies have the power of mirroring multiple biochemical processes and pathways happening in tissues [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs can also be detected in various body fluids such as cerebrospinal fluid (CSF), blood, urine, and saliva ( Lai et al, 2022 ; Zhang et al, 2021b ). Abundant levels of circular RNAs are expressed in the CSF, although these are less diverse than those in the blood ( Wang et al, 2022 ); by contrast, much more diverse and higher levels of circular RNAs are expressed in the blood than in urine or saliva ( Bahn et al, 2015 ; Hutchins et al, 2021 ; Koh et al, 2014 ).…”
Section: Intracellular Circular Rnas As Biomarkers and Therapeutic Ta...mentioning
confidence: 99%
“…CircRNAs have attracted a great deal of attention as cancer biomarkers in recent years. The high stability of circRNAs, especially in body fluids such as plasma, and their potential ability to affect cancer-related pathways have made them suitable biomarkers for managing cancer in various ways, including diagnosis, prognosis, or response to treatment [9] . Recent research showed that up-regulation of hsa_circ_0005092 and hsa_circ_0002647 positively correlated with recurrence-free survival and overall survival in GAC patients [10] .…”
Section: Introductionmentioning
confidence: 99%